The Effect of Sticky Bone with Concentrated Growth Factor on Bone on Socket Preservation and Delayed Implant Placement: A Case Report of Two Cases - K Sitamahalakshmi; Sai Krishna Bingi; Radhika Mandhrachalam; S Keerthi Sai (Wolters Kluwer Medknow Publications, 2024)
As they release and enhance numerous areas for regeneration signaling and maintenance, platelets are energy sources with a wealth of growth factors (GFs). To create sticky bone (SB), concentrated GF (CGF), one of the platelet generations, was combined with a bone transplant. The purpose of this study was to determine how concentrated SB development affects bone density and volume surrounding dental implants. Two patients with grossly decayed tooth or grade III mobile tooth were included in the study. After extraction of the tooth, SB enriched with CGF was placed in the socket and closed with membrane. After 1 month of socket preservation, dental implantation is performed. Loading of implant is performed after 3 months of implant placement. Bone volume and density measurements were performed immediately after socket preservation (T0), 1 month after socket preservation after implant placement (T1), and 3 months after socket preservation loading of dental implants (T2) with cone-beam computed tomography (CBCT). Bone volume and density increased 3 months after socket preservation loading of dental implant (T2) when compared to baseline that is immediately after socket preservation (T0) and 1 month of socket preservation after implant placement (T1). Also, improvement is seen after 1 month of socket preservation. It was observed that SB with CGF shows excellent enhancement in bone formation in quality and quantity of the bone after socket preservation and loading of implant compared with CGF alone.